2009
DOI: 10.1002/ppul.20942
|View full text |Cite
|
Sign up to set email alerts
|

Reference equation for 6‐min walk distance in healthy North African children 6–16 years old

Abstract: This reliable 6-MWD reference equation enriches the World Bank and provides a useful reference for the care of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
80
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 25 publications
12
80
2
1
Order By: Relevance
“…13,15,17,20 Nevertheless, only one of them (Ulrich et al) 20 gave age-by-age reference values (Table 4). This study along with ours demonstrated a decline in the 6MWD after the age of 12; however, both the decline and resurrection of the 6MWD were more obvious in our study.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,17,20 Nevertheless, only one of them (Ulrich et al) 20 gave age-by-age reference values (Table 4). This study along with ours demonstrated a decline in the 6MWD after the age of 12; however, both the decline and resurrection of the 6MWD were more obvious in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Priesnitz et al [33] and Ben Saad et al [34] reported increases in 6MWD with increasing age in children and adolescents, respectively. They associated their results with higher degree of maturation among adolescents when compared with children.…”
Section: Modelmentioning
confidence: 95%
“…The need for reference equations specific to North African populations has been demonstrated for spirometry, [10][11][12][13][14][15] 6-minute walk distance 16,17 and fatfree mass data. 18 The applicability and reliability of published PNIF reference equations and normal values 8,9 should be assessed as regards North African subjects, in order to avoid erroneous clinical interpretation of PNIF data in this population.…”
Section: Introductionmentioning
confidence: 99%